Milling responses of green gram under batch processing - Singh, Sanjay Kumar; Agrawal, U S (Journal of Agricultural Engineering, 2005)
A study was conducted using full factorial design for milling of green gram at 11% db moisture content on Satake Grain Testing mill. Models were developed to represent the milling responses. Minimum milling losses of 10.3% (brokens + powder) were obtained at 10 m/s roller speed, 10 s residence time and 0.5 g/cc dispersal density, whereas the values of coefficient of hulling, coefficient of wholeness of kernel and hulling efficiency at this condition were 79%, 86% and 70%, respectively.